Steric restraints in redox-active guanidine ligands and their impact on coordination chemistry - Engels, Eliane; Koepcke, Hanna; Lörsch, Marko; Römgens, Patrick; Helm, Anna Katharina; Leingang, Simone; Kaifer, Elisabeth; Himmel, Hans-Jörg (Chemistry - a European journal, 2025)
The introduction of redox-active ligands into coordination compounds is attractive for a number of applications; intramolecular electron transfer between a redox-active ligand and a metal is the basis for applications in switchable devices and advanced redox catalysis for multielectron substrate activations. A fine-tuning of the properties of redox-active ligands focusses on the redox potential and frontier orbital energies, as well as the steric demand and coordination mode. In this work, we report the first synthesis of new o-diguanidino-benzene ligands in which the two guanidino groups are connected through an alkyl chain of different length. The introduction of an ethylene bridge between the two guanidino groups turns a strongly coordinating ligand into a noncoordinating molecule, while keeping its strong Brønsted basicity. These features qualify the ethylene-bridged compound as a powerful alternative to Huenig's base, diisopropyl-ethyl-amine. The change from an ethylene to a propylene bridge switches back on the coordination ability. It is also possible to introduce a methyl group to the central C atom of the propylene bridge without loss of nucleophilic properties. The analysis, based on a variety of metal complexes, identifies three structural parameters to assay the structural restraint. Macrocyclic tetraguanidines are also formed.
Zuerst veröffentlicht: 25. Oktober 2025
Gesehen am 02.12.2025